“A good first job”? Migrant workers in Icelandic hotels - Margrét Wendt 1993- (2019)
Mobility has shaped much of our contemporary world, including the tourism industry. In addition to mobile tourists, there is an increasing number of mobile workers who seek employment in the tourism industry. This study presents a qualitative case study from Iceland, where the number of migrant workers in tourism has increased disproportionally, resulting in the industry’s dependency on migrant workers. A total of thirteen semi- structured interviews were taken at three hotels in rural Iceland in order to shed light on the benefits and challenges that employment in the tourism industry creates for migrant workers. In addition, the study presents what benefits and challenges employers face in light of an increasingly diverse workforce. The findings of this thesis indicate that communication and learning are among the key benefits of tourism employment. By interacting with co-workers and guests from various countries, migrant workers can improve their English language skills, increase their cultural knowledge and form transnational ties, which further enhances their transnational mobility. However, the English-speaking environment of the hotels does not provide all workers with the opportunity to improve their Icelandic language skills. This in turn hinders migrant workers from settling in Iceland and participating in wider society. Without an understanding of the host country’s language, migrant workers’ occupational mobility is difficult to increase. Implications for employers and the tourism industry include the need to foster a culture of learning, providing opportunities for learning about the host country and its language. Hreyfanleiki er mótandi afl sem hefur víðtæk áhrif, þar með talið á ferðaþjónustu. Ferðaþjónustan einkennist ekki aðeins af hreyfanlegum ferðamönnum, heldur einnig af hreyfanlegum starfsmönnum sem flytja erlendis og starfa í greininni. Á Íslandi hefur erlendum starfsmönnum í ferðaþjónustu fjölgað gríðarlega undanfarin ár og því reiðir atvinnugreinin sig nú á fjölbreyttan hóp starfsmanna. ...